KINERJA ZAT PEMACU PERTUMBUAHAN DARI CAIRAN RUMPUT LAUT Sargassum polycistum DALAM MENINGKATKAN PERTUMBUHAN KEDELAI (Glycine max L Merril) - Aryanti, Woro Sri; Izzati, Munifatul (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2009)
Sargassum polycistum is one of seaweeds species that grow in Indonesia sea. According to Montano and Tupas (1990), this seaweeds contain plant growth hormone. It has been suggested that Sargassum can be used to enhance the growth of soybean. This research is aimed to study effect of Sargassum extract spraying on growth of soybean. Beside that, it also aimed to determine the best concentration of its extract in enhancing the growth of soybean. This research was designed by completed Randomized Soybean that was applicated with water without extract was served as controls. The growth of soybean evaluated, including number of leave, the increase of plant height, and also fresh and dry weight of soybean. esults indicated that, Sargassum extract can increase the growth of soybean. At concentration of 3000 ppm 5000 ppm, the Sargassum extract increased leave number of soybean plant. The fresh and dry weight of soybean plant was also increased significantly by application of Sargassum extract at concentration of 1000 ppm to 5000 ppm. It can be included that the best growth of soybean was resulted when applicated by Sargassum extract at concentration of 4000 ppm to 5000 ppm. Key words : Sargassum extract, growth hormone, soybean growth rate.